PENINGKATAN KINERJA SUMBER DAYA MANUSIADAN ACTIONABLE KNOWLEDGE QUALITYMELALUI MOTIVASI BERPRESTASIDAN KEPERCAYAAN INTERPERSONAL - Amin Amin (Jurnal Riset Bisnis Indonesia, 2015)
This research was initiated by research gap of the experts research result. Ghafoor, Gillani et al(2013) stated that achievement motivation affected human resources performance, while this wascontroversi to the research of Alam and Mia (2012) which concluded that achievement motivation didnot affect human resources performance. This research paper attempted to estimate the effect ofachievement motivation and interpersonal trust on human resources performance through actionableknowledge quality in Government Region Secretariat of North Konawe Regency. After distributingrelevant questionnaires among 104 employees, all usable questionnaires were returned. Then thedata collected were analyzed by using Structural Equation Modeling with AMOS 18.00 software. Theresearch result to the hypothesis showed that there was a significant positive effect of achievementmotivation to human resources performance and actionable knowledge quality. In contrast, there wasno significant effect of actionable knowledge quality to human resources performance. Furthermorethere was a significant positive effect of interpersonal trust to actionable knowledge quality and humanresources performance in Government Region Secretariat of North Konawe Regency. Implication tothe managerial policy of the research that 1) related to the achievement motivation variable, theorganization should create a conducive work atmosphere which invigorate work motivation, such askeep cleaning, orderliness, noise avoidance, and manage enlightenment more available so that theemployees could enjoy their jobs and loved the challenging job for getting the goal aimed, 2) relatedto interpersonal trust, the organization should build the trustworthiness between all employees, suchas build effective communication between top – low management so that it could trigger the newknowledge creation like collective intelligence, 3) related to the human resources performance, theorganization should increase the employee performance appraisal system, such as job placementbased on employees’ expertise and evaluate every work result so that quantity, quality of work andcontribution to the organization wished always sustainable.Keywords: Achievement Motivation, Interpersonal Trust, Actionable Knowledge Quality, HumanResource Performance